Noninvasive ventilation failure in patients with hypoxemic respiratory failure: the role of sepsis and septic shock - Duan, Jun; Chen, Lijuan; Liang, Guopeng; Shu, Weiwei; Li, Liucun; Wang, Ke; Wang, Shengyu; Liu, Xiaoyi; He, Chunfeng; He, Dehua; Chen, Qimin; Wei, Bilin; et al. (Therapeutic advances in respiratory disease, 2019)
Background: Sepsis and septic shock are common in noninvasive ventilation (NIV) patients. However, studies on the association between sepsis and NIV failure are lacking. Methods: A prospective multi-center observational study was performed in 16 Chinese intensive care units (ICUs). Patients who used NIV due to hypoxemic respiratory failure were enrolled. Sepsis and septic shock were diagnosed according to the guideline of sepsis-3. Results: A total of 519 patients were enrolled. Sepsis developed in 365 patients (70%) and septic shock developed in 79 patients (15%). However, 75 patients (14%) had no sepsis. NIV failure was 23%, 38%, and 61% in patients, with no sepsis, sepsis, and septic shock, respectively. Multivariate analysis found that sepsis [odds ratio (OR) = 1.95, 95% confidence interval (CI): 1.06–3.61] and septic shock (OR = 2.47, 95% CI: 1.12–5.45) were independently associated with NIV failure. In sepsis and septic shock population, the NIV failure was 13%, 31%, 37%, 53%, and 67% in patients with sequential organ failure assessment (SOFA) scores of ⩽2, 3–4, 5–6, 7–8, and ⩾9, respectively. Patients with nonpulmonary induced sepsis had similar NIV failure rate compared with those with pulmonary induced sepsis, but had higher proportion of septic shock (37% versus 10%, p ⩽ 0.01) and lower ICU mortality (10% versus 22%, p ⩽ 0.01). Conclusions: Sepsis was associated with NIV failure in patients with hypoxemic respiratory failure, and the association was stronger in septic shock patients. NIV failure increased with the increase of organ dysfunction caused by sepsis. The reviews of this paper are available via the supplemental material section.